The Impact of Xenophobic Violence on the Integration of Immigrants - Max F. Steinhardt (Institute of Labor Economics (IZA), 2018)
Integration of immigrants is a two-way process involving immigrants and the host country society. An underexplored question is how events of xenophobic violence in the host country affect the integration of immigrants. For this purpose, I exploit a unique series of anti-immigrant attacks in the early 1990s in West Germany. Using a difference-in-differences matching strategy, I find that macro exposure to xenophobic violence has an impact on several dimensions of socio-economic integration of immigrants. In particular, it reduces subjective well-being and increases return intentions, while it reduces investment in German language skills among those staying in Germany. From a policy perspective, this paper shows that anti-immigrant violence can have indirect costs by impairing the integration of those immigrants who belong to the target group of xenophobic attacks.
Keywords: A14; J15; J61; 330; immigration; integration; xenophobia; hate crimes